An unusual presentation of degenerating fibroid - Bhave, Neha V.; Shah, P. K.; Chaudhari, Hemangi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Degeneration in a fibroid is seen when the blood supply falls inadequate to support the center of fibroid. Usually degeneration in a fibroid requires a symptomatic medical management. This is a case report of a degenerating fibroid that uncommonly presented in postpartum period as a retroperitoneal abscess requiring exploratory laparotomy.